PS-073 Regional project: risk management in hospital wards and nursing homes for elderly residents. (24th March 2015) - AdamI, S; Ferrarese, A; Tardivo, S; Leone, R; Conforti, A; Saia, M; Scroccaro, G
Abstract : Background: Risk management is essential for the delivery of safe high-quality social care services. Medicines errors compromise patient confidence in the healthcare system and increase healthcare costs. Purpose: The aim of this exploratory analysis was to detect the status of implementation of the national Recommendations for the safe and secure handling of drugs in hospital wards and nursing homes for the elderly of our Region. Material and methods: The project was conducted in some hospital wards (n = 210) and nursing homes for elderly residents (n = 67). The survey involved all public hospitals (21 AULSS, 2 University Hospitals, 2 IRCCS) and 16 private hospitals of the region. Nursing homes were recruited by AULSS. The project was carried out by pharmacists through visits to the hospital wards and nursing homes, interviews with medical/nursing staff, direct observation and checks. Data were collected between July–October-2013 in a database and analysed by a multidisciplinary working group (pharmacists, pharmacologists, clinicians, nurses). Results: The project has showed, both in hospital wards and nursing homes, some critical issues: low adoption of procedures on medicines reconciliation (34% and 30%); patients' allergy information not consistently documented in the clinical record (74% and 69%); low reporting rates of ADRs (11% and 4%). Moreover, 35% of hospital wards and 46% of nursing homes did not store look-alike-sound-alike drugs (LASA) in different locations or use alert stickers on shelves where LASA drugs were present. Conclusion: There is the need to develop a risk management culture, both in hospital wards and in nursing homes. A regional multidisciplinary working group will develop a medicines reconciliation process, in order to improve the transitions of care throughout the hospitals/nursing homes and within the practice setting. Moreover, we need to take initiatives to encourage healthcare professionals to report ADRs and to encourage them to manage risks systematically. Reference: ASHP_Guidelines_on_Preventing_Medication_Errors_in_Hospitals No conflict of interest.